STUDI KOMPREHENSIF TERHADAP RISIKO PEMBIAYAAN PADA BANK DIGITAL SYARIAH - Muhammad Bahanan; Hardian Dwi Utomo (LPPM Sekolah Tinggi Agama Islam Al-Utsmani Bondowoso, 2025)
This study provides a comprehensive analysis of the various financing risks faced by Islamic digital banks in Indonesia as a consequence of the rapid development of digital technology in the Islamic financial system. Using a qualitative approach based on literature review, the research explores several types of risks including credit risk, sharia compliance risk, operational risk, liquidity risk, reputational risk, and information technology risk in the operational activities of Islamic digital banking. The findings reveal that although digitalization enhances efficiency and financial inclusion, it also introduces new challenges in risk management that must comply with Islamic principles. The underlying factors contributing to these risks include the uncertainty of Islamic contracts, the quality of customer profiles, technological vulnerabilities, regulatory compliance with sharia law, and low levels of financial and digital literacy. This study also proposes relevant mitigation strategies such as the application of AI and big data in credit scoring, strengthening IT security infrastructure, and optimizing the role of the Sharia Supervisory Board. The results of this study are expected to serve as a reference for the development of adaptive and sharia-compliant risk management systems for Islamic digital banks in the modern era.